Experimental Research Into Generation of Acoustic Emission Signals in the Process of Friction of Hadfield Steel Single Crystals - Lychagin D. V. Dmitry Vasilievich; Filippov A. V. Andrey Vladimirovich; Novitskaia O. S.; Kolubaev Е. А. Evgeny Aleksandrovich; Sizova O. V. (2016, 2016)
Title screen